P690 Pulmonary valve endocarditis complicated with fistula between right ventricle outflow tract and aorta in a patient with patent ductus arteriosus. (17th January 2020) - Toader, D; Craciun Mirescu, A; Cocora, M; Munteanu, O; Mustafa, E R; Florescu, C; Berceanu, M; Popescu, M; Cojocaru, A; Oprian, A
Abstract: Background: The majority of cases of right sided infective endocarditis involve the tricuspid valve. Isolated pulmonary valve (PV) endocarditis is rare. Congenital heart disease are risk factors. Material and methods: We present the case of 36 years old male, without any known cardiovascular disease, who was admitted with signs and symptoms of heart failure, pulmonary embolism and fever. He was evaluated clinically, 12 lead ECG, pulmonary radiography, thoracic computer tomography (CT) scan, transthoracic and transesophageal echocardiography, laboratory investigations. Results: Transthoracic and transesophageal echocardiogram revealed large vegetations located on pulmonary valve, pulmonary regurgitation and dilation of the pulmonary valve, patent ductus arteriosus (PDA) with bidirectional shunt and local complications: fistula between right ventricle outflow tract (RVOT) and aorta, pleural and pericardial effusion. Blood cultures were negative. ECG aspect was right bundle branch block. Radiography and thoracic CT scan revealed pulmonary embolism aspect. The patient was treated with antibiotics and surgical option included debridement of the infected area, vegetation excision with valve replacement, relief of RVOT, fistula closure with pericardial patch and ligature of PDA. Evolution after surgical intervention was good.Conclusions: This presentation reveals a favorable evolution of a patient with infective endocarditis located to pulmonary valve. In most of cases, right heart endocarditis presents with signs and symptoms of respiratory disease and fever; these are due to septic pulmonary embolization. Isolated PV endocarditis still remains a challenging and needs carefully echocardiographic evaluation for a correct diagnosis and risk factors identification.